MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA GUNUNG PICUNG, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Nurhasan, Abdul Khodir; Hidayatullah, Taufik (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This Community Service aims to design Islamic microfinance institutions. The subject of this community service is the community of Gunung Picung Village, Pamijahan District, Bogor Regency, West Java Province.This service is intended for Islamic microfinance institutions so that MSMEs get more fulfilled financing and get the right customers. With limited business capital in the village of Gunung Picung Islamic microfinance institutions can provide capital and make the business better.the method used in this study is the method of approach to the community.Islamic microfinance institutions are financial institutions that are relied on for the community when they want to need money for business capital or any form of need. With this dedication, it can be concluded that financial institutions must choose the right customers in order to prosper the community, MSME actors and provide benefits for financial institutions.